American dream in novels The Grass Roof and East Goes West: The Making of an Oriental Yankee by Younghill Kang - Benešová, Kateřina Sofie (Univerzita Pardubice, 2022)
This bachelor thesis deals with the theme of the American Dream in novels of Younghill Kang and how it is depicted. The first chapter focuses on the American dream itself, its history and what it entails. The second chapter describes immigration from Asia to the USA and the model minority. In the third chapter, the author is introduced, along with literary context of the novels and literary devices. The two analytical chapters target East Goes West and The Grass Roof, with the main themes being disillusion, social prejudice and the attainment of the American Dream.
Americký sen v románech The Grass Roof a East Goes West: The Making of an Oriental Yankee autora Younghilla Kanga
Keywords: Kang, Younghill; americký sen; East Goes West; Drnová střecha; asijsko-americká literatura; deziluze; Kang, Younghill; American Dream; East Goes West; The Grass Roof; Asian American literature; disillusion